PENGUBURAN MASYARAKAT DAYAK1 DAN TORAJA DALAM PERBANDINGAN - Hartatik, nfn (Balai Arkeologi Kalimantan Selatan, 2007)
Both the Dayak in Kalimantan and the Toraja in Sulawesi have same meaning of term, that is man who live in hinterland. There are several similarities in religion concepts and burial equipments between the Dayak and the Toraja. For examples, the burial ceremonies which scarify lots of animals and the use of boat - like containers. This paper reviews the comparation of religion concept specially the burial methods of both of ethnic. Theories which explain the relationship between both ethnics are not yet defined, therefore his paper constitute a preliminary stage to examine such relationship